Perceptions of mental illness among the Ndebele culture, in the community of Middelburg, Mpumalanga Province - Mahlangu, Nonkululeko Gladness (My University, 2018)
Mental illness is conceptualised differently across cultural and religious groups. How it is explained, understood, diagnosed and treated depends on how society and culture interpret it. The western way in which knowledge is generated with regards to the acknowledgement of the value of African indigenous systems of knowledge, that marginalises African systems of knowledge calls for an inclusive evaluation of such culturally-based studies. African traditional societies, such as the Ndebele, are rich in indigenous knowledge systems and can contribute to practices and social values by enhancing the enactment of understanding a community, culturally, and holistically. This stipulates that perceptions of mental illness and certain specific aspects of Ndebele cultural practice and belief systems will be explored, in relation to South African research done in this area. With this said, the area of enquiry this study is dwelling upon, is that of indigenous traditional healing, as this is strongly reflected in the findings and the discussion on the perceptions of the etiology and treatment of mental illness. This study seeks to explore perceptions of mental illness among Ndebele community members in the Mpumalanga Province and the possible role that their culture plays on their perceptions. The study was directed at gaining an understanding of the experiences of treatment and overall exposure to mental illness within the community using the Biopsychosocial model and its extension, the Biopsychosocial-Spiritual model, as the theoretical framework. A qualitative research method was used, employing a non-probability snowball sample of 12 participants. Semi-structured interviews were conducted and analysed using interpretative phenomenological analysis. The findings of the study emphasise the importance of the Ndebele culture in day-to-day living. The themes that were found that relate to the Ndebele culture are the fact that mental illness is dealt with as a sub-culture; the causes and treatment of mental illness; and the stigma attached to people who suffer from mental illnesses. The results of mental illness among the Ndebele traditions show that mental illness is affected by cultural influences, social influences and environmental influences.
A research report by Masters of Arts in Psychology by Coursework and Research Report Department of Psychology University of the Witwatersrand 2018
Keywords: Mental illness; Mental illness--South Africa